2017
DOI: 10.1080/02713683.2017.1337157
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Diagnostic Ability of the Optical Coherence Tomography Angiography Vessel Density Parameters

Abstract: The glaucomatous eyes showed decreased vessel density as determined by OCT angiography. Although the peripapillary vessel density parameters showed similar glaucoma diagnostic ability with circumpapillary RNFL thickness, in the early stage, the vessel density parameters showed limited clinical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 28 publications
11
82
2
2
Order By: Relevance
“…Evaluations of the macular VD parameters in PPG eyes were not extensive [8,26,29,30]. Our study showed significant macular microvasculature dropout in PPG and early PG eyes, which was supported by Hou et al [30] and Poli et al [29].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Evaluations of the macular VD parameters in PPG eyes were not extensive [8,26,29,30]. Our study showed significant macular microvasculature dropout in PPG and early PG eyes, which was supported by Hou et al [30] and Poli et al [29].…”
Section: Discussionsupporting
confidence: 85%
“…Structural parameters in the macular region such as the ganglion cell complex (GCC) or ganglion cell-inner plexiform layer have been found to be thinner in eyes with pre-perimetric glaucoma (PPG) than in healthy eyes [21][22][23][24][25]. However, only a few studies have focused on macular microcirculation changes in early glaucoma [26][27][28][29][30]. Among these studies, fewer have focused on PPG [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Regional diagnostic abilities for early stage glaucoma were comparable to those found by Chung et al [21] with the highest AUC for inferotemporal sector (AUC = 0.74) and the lowest for temporal area (AUC = 0.58).…”
Section: Diagnostic Abilitysupporting
confidence: 69%
“…This result is consistent with the study by Rao et al [20], who found a difference in the median vessel densities in the macula between the glaucoma (mean MD -5.3 dB) and the control eyes, even if of small magnitude (between 3 and 6%). In the recent study by Chung et al [21], the macular superficial vessel densities in the 3 × 3 scan were lower in the glaucomatous eyes at moderate stage than in healthy eyes. However, macula vessel densities did not differ between the control and the early glaucoma group (mean MD = -2.42).…”
Section: Macular Vdmentioning
confidence: 99%
“…Allerdings ist der klinische Wert der OCTA besonders im Frühstadium des Glaukoms unverändert unsicher [4]. …”
Section: Transfer In Die Praxis Von Prof Dr Klaus Rohrschneider (Heunclassified